To study the relationship between bank layout and customer satisfaction - Norazlina, Rusli (2013)
Layout design is an important element for any organization to maintain their customer loyalty. Many importance and benefit can be obtained by any organization when the customer satisfaction can be achieved when implementing the systematic and efficiently layout design. This research is carried out to study the relationship between bank layout and customer satisfaction. The objective of this research is to study the relationship between Bank layout and customer satisfaction and to determine suitability of current layout arrangement. One of the commercial bank located in Kuantan, Pahang was selected as a scope for this study. Participant randomly selected and the customers of bank are the respondent to answer the questionnaire in this study. Two instruments were used to collect data which is survey questionnaire which consist of open-ended and closed-ended questions. Observation also used in this study because to see the phenomenon or the environment and arrangement layout of bank. The participants are 100 randomly selected customers from different age, gender, race and so on. The result showed that environment (Independent Variable) and counter (Dependent Variable) is the factors that influence the layout design and customer satisfaction. The correlation showed that layout and customer satisfaction have a strong relationship and the current layout arrangement of bank in an irregular situation or not effective and efficient condition.